A Neglected Parasite: Macracanthorhynchus hirudinaceus, First Report in Feral Pigs in a Natural Park of Sicily (Southern Italy) - Migliore, Sergio; Puleio, Roberto; Gaglio, Gabriella; Vicari, Domenico; Seminara, Salvatore; Sicilia, Elio Rodolfo; Galluzzo, Paola; Cumbo, Valentina; Loria, Guido Ruggero (Frontiers in Veterinary Science, 2021)
Sanitary management and population control of feral pigs remains a major problem in public health, particularly in natural parks where hunting is prohibited and the extensive farming of livestock is common. Macracanthorhynchus hirudinaceus is a zoonotic parasite species with a worldwide distribution of which the natural definitive hosts are primarily pigs and wild boars (Sus scrofa). The present study describes the main anatomo-pathological and parasitological findings in the first outbreak of M. hirudinaceus in feral pigs in a natural park of Sicily (South-Italy). Overall, 52 acanthocephalans were collected from the small intestine of four infected feral pigs. The prevalence among the 36 examined animals was 11.1% with a mean Abundance (mA) and the mean Intensity (mI) of 1.4 and 13 respectively. Pathological examination revealed grossly visible nodules on the external surface of intestine, corresponding to the proboscis of M. hirudinaceus attached deeply into the intestinal wall. In these sites, severe inflammatory reactions in the involved tissue and the destruction of normal intestinal architecture, as well as necrosis and ulceration in the mucosa, submucosa and part of the muscolaris mucosae were described. This is the first official report of this neglected zoonosis in Italy, in particular in a natural park where the extensive farming of domestic pigs is practiced. This could favor the spread of this parasite in domestic animals and environment, increasing the accidental risk of infection in human residents of these areas.